Evaluation of the anti-snakebite, antimicrobial and antioxidant potential of Philodendron megalophyllum Schott (Araceae), traditionally used in accidents caused by snakes in the western region of Pará, Brazil - Costa Guimarães, Noranathan da; Freitas-De-Sousa, Luciana Aparecida; Souza, Maria Carolina Scheffer de; Oliveira de Almeida, Patrícia D.; Santos, Maria Cristina dos; Nunez, C. V.; Bezerra de Oliveira, Ricardo; Mourão, Rosa Helena Veras; Moura, Valéria Mourão de (Toxicon, 2020)
Ethnopharmacological relevance: In the region of Western Pará, Amazonia, Brazil, Philodendron megalophyllum is widely used for the treatment of envenomations caused by bites from venomous snakes. The traditional use of plants is usually done through oral administration of an infusion (decoction) soon after the bite occurs. The efficiency of aqueous extracts of P. megalophyllum was demonstrated for blocking the activity of the venom of Bothrops sp., but only for a pre-incubation protocol (venom:extract), which fails to simulate the real form of use of this species. In this context, the objective of this research was to evaluate the anti-snakebite potential of the aqueous extract of P. megalophyllum to inhibit for the biological activity induced by Bothrops atrox venom (BaV) using traditional treatment methods. Material and methods: Initially, an aqueous extract using the stem of P. megalophyllum (AEPm) was prepared following the standard procedure used by the residents of the rural area along the Tapajós River (Eixo Forte region) in Santarém, PA, Brazil. The phytochemical profile of AEPm was conducted using thin layer chromatography (TLC) and phenolic compounds were quantified through colorimetric trials. The cytotoxicity of AEPm was evaluated using the MRC-5 human fibroblast line, and the antioxidant potential was measured using DPPH methods and cell culture. AEPm antimicrobial action was evaluated by the 96-well plate microdilution and the minimum inhibitory concentration (MIC) methods using 18 types of microorganisms including bacteria that are present in the oral cavity of snakes. AEPm blocking potential was tested against BaV activity in vitro (fibrinolytic) and in vivo (defibrinating and hemorrhagic). In order to test for an interaction between BaV and AEPm SDS-PAGE electrophoresis was conducted. Results: The presence of coumarins, fatty acids, and hydrolysable tannins were detected in the AEPm. The colorimetric trials showed that AEPm had a high concentration of condensed tannins (20.1 ± 1.2%). The potential of AEPm for blocking of hemorrhagic and fibrinolytic activity of BaV showed a maximum reduction of 86.1% and 96.5%, respectively, for the pre-incubation protocol (1:10, venom:extract). However, when the extract was administered orally there was no significant blocking of these activities. The interaction of BaV and AEPm showed a modification of the profile of proteic bands when compared to the pattern of bands obtained from the BaV alone. The AEPm was not considered toxic, demonstrated antioxidant activity, and was capable of reducing the growth of 10 of the 18 studied microorganisms. Conclusion: Although the stem of P. megalophyllum is indicated by traditional medicine techniques as effective against snakebites, the extract, when tested orally was not able to significantly inhibit (p ˃ 0.05) hemorrhage and defibrinating activity induced by the B. atrox venom. On the other hand, the extract yielded a promising result with respect to antioxidant and antimicrobial potential, and after further studies it could be used as a complementary treatment for localized action and secondary infections that frequently occur with snakebites from the genus of Bothrops sp. © 2020 Elsevier Ltd
Keywords: Coumarin; Doxorubicin; Fatty Acid; Phenol; Philodendron megalophyllum extract; Plant Extract; Tannin; Unclassified Drug; animal experiment; animal model; Anti-microbial Activity; Antioxidant Activity; Bothrops; Brazil; Colorimetry; Controlled Study; Cytotoxicity; Dpph Radical Scavenging Assay; Ethnopharmacology; Human; Human Cell; Male; Minimum Inhibitory Concentration; Mouse; MRC-5 cell line; Nonhuman; Philodendron; Philodendron megalophyllum; Phytochemistry; Plant Stem; Electrophoresis, Polyacrylamide Gel; Priority Journal; Rural Area; Snakebite; Chromatography, Thin Layer; Medicine, Traditional; en